Etnofaulismos e os dicionários monolíngues brasileiros - Kasama, Deni Yuzo [UNESP] (2015)
Throughout history, migratory movements have led to the emergence of derogatory meanings and terms used by one group to label another. Such phrases, built on stereotypical and prejudiced views, first occurred in the lexicon of the languages and later began appearing in dictionaries. A common lexicographical practice called labeling states that these derogatory meanings should present diaevaluative information (i.e. a usage feature relating to a particular attitude or evaluation), warning the dictionary user about their controversial nature. Nevertheless, this practice is not always methodical, and contemptuous meanings often receive other usage labels such as semantic transition that do not clearly indicate their offensive impact. Thus, we sought to investigate the usage labels in Brazilian monolingual dictionaries as well as other issues relevant to dictionary making, such as the presence of a dominant ideology, the descriptive versus prescriptive role of the dictionary, and the corpus composition that forms the base of the lexicographical product. In this study, we investigated four unabridged Brazilian monolingual dictionaries (Aulete Digital, Aurélio, Houaiss and Michaelis) and analyzed eighty-seven foreign disparaging allusions, herein called ethnophaulisms (ROBACK, 1944), featuring 19 different usage labels and divided in seven macro-categories (semantic transition, diatopic, diaphasic, diastratic, diachronic, diafrequent and diaevaluative). We analyzed microstructural elements, such as usage labels, that help dictionary users identify which lexical items generate controversy. Although these elements were included, the practice was not systemic or homogenous, invalidating the descriptive role of the dictionary. This lack of consistency is also reflected in the haphazard inclusion or exclusion of contemptuous meanings frequently present in unconventional corpora such as social networks (in this research the microblogging ...